Crossroads of Neurology and Virology: The Neurological Manifestations of COVID-19 - Kirolos Eskandar (Ukrainian Neurosurgical Journal)
Introduction: The COVID-19 pandemic, caused by SARS-CoV-2, has led to an unprecedented global health crisis. While primarily recognized for its respiratory implications, the virus has shown a significant affinity for the nervous system, resulting in a wide spectrum of neurological manifestations. This literature review explores the intersection of neurology and virology, focusing on the acute and long-term neurological effects of COVID-19. Methods: A comprehensive review of current literature was conducted using databases such as PubMed, Scopus, and Web of Science. Relevant studies were selected based on their focus on the pathophysiology, clinical presentations, and long-term neurological outcomes of COVID-19. Special attention was given to peer-reviewed articles, meta-analyses, and clinical case reports published between 2019 and 2024. Results: The review identifies multiple mechanisms by which SARS-CoV-2 invades the nervous system, including direct viral entry and systemic inflammation. Acute neurological manifestations include encephalitis, stroke, and Guillain-Barré syndrome, while long-term sequelae encompass cognitive impairment, neurodegeneration, and psychiatric disorders. The findings underscore the complexity of COVID-19’s impact on the nervous system, with both immediate and enduring effects. Conclusion: Neuro-COVID represents a significant and evolving challenge in the context of the pandemic. Understanding the neurological implications of COVID-19 is crucial for improving patient outcomes and guiding future research. This review underscores the need for heightened clinical awareness and a multidisciplinary approach to effectively address the complex neuro-COVID spectrum.